Synthesis Dithizone-Immobilized In Polivinyl Chloride Membranes For Copper Detection in Water - Pratiwi, Yussi; Febrian, Yogi; Klaudia, Angelina (Chemistry and Materials, 2024)
A simple, cost-effective, and environmentally friendly analytical method is needed to determine Cu (II) levels in water. Many methods have been developed by immobilizing dithizone in a polyvinyl chloride (PVC) matrix with dioctyl phthalate (DOP) as a plasticizer in a tetrahydrofuran (THF) solvent. However, the optimal composition of PVC, DOP, and THF has not been determined. The purposes of this study were to determine the optimal composition of dithizone, PVC, and DOP for the sensor membranes, evaluate the performance of the chemical sensors in detecting Cu (II) ions, and measure the copper content in conventional drinking water. The research began with the fabrication of sensor membranes, followed by absorbance testing, and concluded with method validation through characterization. Adsorption of Cu (II) caused the membrane colour to change from yellow to reddish orange, with maximum absorbance observed at 427 nm. The sensor membrane exhibited the best response to Cu (II) ions at pH 2.8. A linear calibration curve for Cu (II) was obtained in the concentration range of 0-0.6 ppm, with an R² value of 0.9924. The limit of detection was 1.9881 x 10⁻³ mg L⁻¹, and the limit of quantification was 6.0245 x 10⁻³ mg L⁻¹. The molar absorptivity was 9.4831 x 10⁴ L mol⁻¹ cm⁻¹. The proposed sensor membrane was used to measure Cu (II) in drinking water employing the internal standard addition method, with observed recoveries ranging from 98.63% to 100.29%. The copper levels in the drinking water samples tested in this study did not exceed the drinking water quality standards set by PERMENKES RI number 492/PER/IV/2010.